IMPLEMNTASI PROGRAM KELURGA HARAPAN (PKH) DI KECAMATAN BOJONGGENTENG KABUPATEN SUKABUMI - Nasihin, Muhammad Zaeni; Luthfie, Muhammad; Rusliandy, Ruslinady (Administratie: Jurnal Administrasi Publik, 2020)
The Indonesian government seeks to tackle poverty problems by issuing a policy, namely the Family Hope Program. The Family of Hope Program is a social protection program through the provision of cash assistance to poor families who meet the predetermined requirements in this case aiming to improve the quality of education, health and community welfare. The purpose of this study is to determine how the implementation of the Family Hope Program in Bojonggenteng District, Sukabumi Regency and the concept.of Implementing the Hope Family Program in Bojonggenteng District, Sukabumi Regency. The research method used is descriptive qualitative research method, the focus of the research is communication, resources, dispositions and bureaucratic structures. The technique of collecting data is through literature study, observation and interviews, using data validation using triangulation techniques. The results of this research suggest that the implementation of the Family.Hope Program in the District of Bojonggenteng has not been well implemented. Socialization problems and the existence of social disparities between communities are inhibiting factors in the family hope program in Bojonggenteng district. Therefore, the concept of implementing the family hope program in Bojonggenteng sub-district needs evaluation and re-supervision of all stakeholders involved so that an effective hope family program can be implemented.